A compromised multi-objective solution using fuzzy mixed integer goal programming for market-based short-term unit commitment problem - Lotfi, M M; Ghaderi, S F (The Journal of the Operational Research Society, 2014)
When implementing, the solution of single-objective unit commitment models may be dissatisfactory or inapplicable. This might mainly be due to not considering the secondary conflicting objectives from the policy-making in internal/external environment of generation companies in the developed models. To attain a practical compromised multi-objective solution for the short-term unit commitment in the deregulated hybrid markets, a novel fuzzy mixed integer linear goal programme is developed in which several complementary objectives with lower relative importances are also incorporated. Non-linear characteristic curves of the generating units are approximated through the piece-wise linear functions. The fuzzy approach is proposed to handle the imprecise nature of the goals' target levels and priorities as well as some critical data. The critical aspects of power systems are considered in the model. The efficiency of the proposed approach is demonstrated using the experimental results inspired by a real case. The applicable nice feature of our model is that it can easily and efficiently be matched with a various line of unit commitment problems.